STRATEGI PEMERINTAH DAERAH DALAM PENANGGULANGAN KEMISKINAN PASCA PANDEMI COVID-19 PERSPEKTIF EKOLOGI MANAJEMEN DI KABUPATEN NIAS - Fetriaman Telaumbanua; Ayler Beniah Ndraha (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. The Covid-19 pandemic has had a serious impact on poverty in Nias District. This research explores the strategies adopted by the Nias Regency Government in overcoming post-pandemic poverty, taking into account the management ecological perspective. The choice of this topic is based on the urgency of tackling poverty as a socio-economic impact of the Covid-19 pandemic. This research method uses a qualitative approach, including in-depth interviews with stakeholders and the public as well as direct observation. The results of the study revealed that the local government of Nias Regency has implemented various strategies, such as strengthening the local economy, providing social assistance to the community. Management ecology is integrated into the strategy, with a focus on sustainable natural resource management and active community participation. The results of this study underscore the importance of a poverty alleviation strategy by the Nias district government. Implementation of an ecology-based strategy can increase community resilience to the poverty crisis due to the Covid-19 pandemic, as well as create jobs and community economic recovery. This conclusion emphasizes the need for a holistic approach in post-pandemic policies to ensure economic, social and environmental sustainability in Nias District .